Morphological identification and description of three rice root nematodes occurring in China - MEI Yuan-yuan; GUO Kai; ZHENG Jing-wu (浙江大学学报. 农业与生命科学版, 2009)
According to the morphological characters and morphometrics, three species in genus Hirschmanniella were identified. They were H. oryzae, H. mucronata and H. gracilis. Some morphometrics of H. oryzae and H. mucronata varied slightly from the original descriptions of type specimens, most of other morphometric data were within the reference value range. Compared to the original descriptions of type specimen, the data of H. gracilis were smaller. This was the first report of H. gracilis in Zhejiang Province, eastern China.